2022
DOI: 10.3390/molecules27093006
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Dipeptidyl Peptidase III Inhibitors: From Small Molecules of Microbial or Synthetic Origin to Aprotinin

Abstract: Dipeptidyl peptidase III (DPP III) was originally thought to be a housekeeping enzyme that contributes to intracellular peptide catabolism. More specific roles for this cytosolic metallopeptidase, in the renin-angiotensin system and oxidative stress regulation, were confirmed, or recognized, only recently. To prove indicated (patho)physiological functions of DPP III in cancer progression, cataract formation and endogenous pain modulation, or to reveal new ones, selective and potent inhibitors are needed. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…However, this is just one example among over 80 MUTYH missense and truncating variants whose functions are unclear. , There is also evidence that designing novel pharmaceuticals to target enzymes involved in DNA repair pathways may afford successful cancer treatments by increasing the efficacy of anticancer drugs or targeting DNA-repair defective cancers, and highly specific and potent small molecule inhibitors have already been designed for enzymes that share mechanistic features with DNA glycosylases like MUTYH. However, to aid the prediction of the dysfunction of MAP-related MUTYH variants in humans and develop possible cancer treatment strategies, the atomic level details of the chemistry facilitated by MUTYH are required. Indeed, structural information has proven essential for the rational development of small-molecule (transition state analogue) inhibitors. …”
Section: Introductionmentioning
confidence: 99%
“…However, this is just one example among over 80 MUTYH missense and truncating variants whose functions are unclear. , There is also evidence that designing novel pharmaceuticals to target enzymes involved in DNA repair pathways may afford successful cancer treatments by increasing the efficacy of anticancer drugs or targeting DNA-repair defective cancers, and highly specific and potent small molecule inhibitors have already been designed for enzymes that share mechanistic features with DNA glycosylases like MUTYH. However, to aid the prediction of the dysfunction of MAP-related MUTYH variants in humans and develop possible cancer treatment strategies, the atomic level details of the chemistry facilitated by MUTYH are required. Indeed, structural information has proven essential for the rational development of small-molecule (transition state analogue) inhibitors. …”
Section: Introductionmentioning
confidence: 99%
“…Dipeptidyl peptidase-III (DPP-III; EC 3.4.14.4) is a proteolytic enzyme which catalyzes hydrolytic cleavage of dipeptides from peptide substrates (from the N-terminal side). It was isolated from extracts of the bovine pituitary gland and showed relatively high specificity against a series of peptides, i.e., from tetrapeptides to oktapeptides [ 111 ]. DPP-III exhibits a high affinity to bioactive peptides, anigotensins (angiotensin-2, angiotensin-3), enkephalins, and endomorphins.…”
Section: Discussionmentioning
confidence: 99%
“…DPP-III exhibits a high affinity to bioactive peptides, anigotensins (angiotensin-2, angiotensin-3), enkephalins, and endomorphins. It hydrolyzes pentapeptides and Leu- and Met-enkephalin at the Gly2–Gly3 bond as the so-called enkephalinase B [ 80 , 111 ]. Leu-enkephalin is an important brain neurotransmitter that interacts with morphine receptors and reduces pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ang II forms a cis-peptide in a wheel-like conformation between histidine-6 and proline-7 during hydrolysis ( 99 ), meanwhile the binding site of DPP3 can bend to fully accommodate upon binding to Ang II and catalytic substrate. It was found that purified angiotensin-(1–7) [Ang-(1–7)] peptidase and DPP3 exhibited the same Ang-(1–7) hydrolysis profile, and both enzymatic activities were inhibited by the metallopeptidase inhibitor JMV-390 ( 100 ). DPP3 can sequentially hydrolyze Ang-(1–7) to Ang-(3–7) and rapidly convert Ang-(3–7) to Ang-(5–7) ( 101 ).…”
Section: Biological Propertiesmentioning
confidence: 99%